Utilization of waste cooking oil (WCO) in Hot Mix Asphalt (HMA) - Bujang, Mastura; Wan Azahar, Wan Nur Aifa; Jusli, Euniza (IGI Global, 2020)
The use of WCO in binder modification is widely explored in response to waste management issue. A chemical treatment was proposed to reduce the acidity of the WCO that causes its poor performance. Therefore, this chapter evaluates the performance of binders modified with untreated and treated WCO. The physical and rheological tests of binder were conducted to determine optimum percentages of untreated and treated WCO in the binder. The optimum WCOs were utilized for mechanical performance evaluation of Hot Mix Asphalt (HMA) mixture through resilient modulus and dynamic creep. The test showed the failure temperature of binder modified using the treated WCO has increased to 70°C and the treated WCO mixture recorded superior performance by being less susceptible to permanent deformation as compared to the control mix. In conclusion, the chemical treatment had improved the treated WCO performance in the modified binder as asphalt paving materials